Knowledge and attitude towards epilepsy among rural residents in southern Ethiopia: a cross-sectional study - Alemayehu Molla; Birhanie Mekuriaw; Endashaw Habtamu; Moges Mareg (BMC, 2021)
Abstract Background Although epilepsy is one of the most prevalent neurological problems, it is highly surrounded by stigma and prejudice, which results in negative attitude towards the illness. Due to numerous misconceptions and beliefs attributed towards epilepsy, most people in rural communities have poor understanding and perception about epilepsy. Studying knowledge and attitude of this major neurologic problem among rural residents is crucial to add knowledge and show area of interventions. Therefore, the aim of this study was to assess the knowledge and attitude towards Epilepsy among rural residents in Ethiopia. Methods This was a community based cross-sectional study conducted in rural parts of Gedeo zone, Southern Ethiopia. A total of 732 randomly selected adult residents were interviewed using a pre-tested questionnaire. The collected data were entered to Epi-data version 3.1 and analyzed using SPSS version 20. Descriptive statistics and logistic regressions were performed. Multivariable binary logistic regression analysis was conducted to determine the presence of a statistically significant association between explanatory variables and outcome variables at corresponding 95% CI. Results The magnitude of poor knowledge and unfavorable attitude towards epilepsy were 27.0 and 51.6%, respectively. Participants who can't read and write, having stigma related to epilepsy, participants who did not live with epileptic patients; unfavorable attitude and age were factors associated with poor knowledge towards epilepsy. On the other hand, Stigma related to epilepsy, poor knowledge, age and perceiving epilepsy as a God punishment for sinful activities were variables significantly associated with unfavorable attitude of epilepsy. Conclusions There is a gap regarding the knowledge and attitude towards epilepsy among community residents in southern Ethiopia. This demonstrates a need for community educational program regarding epilepsy which can increase community awareness particularly in rural areas to decrease stigma and negative beliefs towards epilepsy.